Pengaruh CAR, NPF, FDR, Inflasi dan BI Rate terhadap Profitabilitas Perusahaan Perbankan Syariah di Indonesia Periode 2014-2018 - Nanda Nur Aini Fadillah; R.A. Sista Paramita (Jurnal Ilmu Manajemen, 2021)
This study aims to analyze whether internal and external factors can affect Sharia banks' profitability in Indonesia because data is viewed data that the profitability of Sharia banks in Indonesia is increasing. However, Sharia banks' development decreases from the number of Sharia bank offices in Indonesia that remain even declining annually. The population used in this study is 14 Islamic commercial banks in Indonesia which the Financial Services Authority registers (OJK) rather than those filtered using specific criteria as stipulated during 2014-2018 in Indonesia and published financial statements for all periods of study and finally gained ten banks, this type of research is a quantitative causal. The results showed that one of the internal factors of the Capital Adequacy Ratio (CAR) had a positive influence over Sharia banking profitability (ROA) and other variables such as Non-Performing Finance (NPF), Financing of Debt Ratio (FDR), inflation, and BI Rate had no effect on Return On Asset (ROA).